URGENSI PENCATATAN NIKAH DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF (Studi Kasus Terhadap Pemahaman Masyarakat Desa Tellangkere Kecamatan Tellu Limpoe) - Darmi; Lomba Sultan; Nurfaika Ishak (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
This study discusses the urgency of marriage registration in the perspective of Islamic law and positive law (a case study on the understanding of the people of Tellangkere Village, Tellu Limpoe District). This study discusses the Process of Marriage Registration in Normative Studies (Islamic Law and Positive Law) and the factors that influence people's understanding of marriage registration. The type of research used in this thesis is a qualitative research type. The approach used is a normative juridical approach. The results of the study have shown that the process of registering marriages in the perspective of Islamic law and positive law is not in line with existing regulations. Where people think that the marriage book or marriage certificate itself is not important. Marriage registration employees or the KUA office have made it easier to manage marriage certificates. Many people view that a legal marriage is a marriage carried out only religiously, so that it becomes an obstacle in determining marriage registration. However, if it is not registered with the KUA, then the marriage is not legally valid, so that many people feel a bad impact on the continuity of the household they live. Like the child does not have a birth certificate, when a divorce occurs, the wife cannot sue her husband for the property and does not have legal force. Factors that influence the understanding of the people of Tellangkere Village about marriage registration are economic factors and social factors. Keywords: Marriage Registration, Islamic Law, Positive Law.